If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -5 = 4x + -6 Reorder the terms: -5 + -3x = 4x + -6 Reorder the terms: -5 + -3x = -6 + 4x Solving -5 + -3x = -6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + -3x + -4x = -6 + 4x + -4x Combine like terms: -3x + -4x = -7x -5 + -7x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + -7x = -6 + 0 -5 + -7x = -6 Add '5' to each side of the equation. -5 + 5 + -7x = -6 + 5 Combine like terms: -5 + 5 = 0 0 + -7x = -6 + 5 -7x = -6 + 5 Combine like terms: -6 + 5 = -1 -7x = -1 Divide each side by '-7'. x = 0.1428571429 Simplifying x = 0.1428571429
| 685=85-2x | | a=bh/2 | | (8+2x)5=-28x+2 | | -4(x+2)=-8 | | 1.5(2e-30)+2e=135 | | 3.7j+1.9=16.7 | | (16a^5b^-5)^-4/(2a^6b^-2)^-4 | | 6-3=x | | 9/103 | | y(8x-9y)dx+2x(x-3y)dy=0 | | 3xy=20 | | x^2+6=-9x | | x(-3/11-5/9x)=0 | | -4y-8=4(2y+3) | | 24x^3+18x^2-6x= | | 2.1x-8.6=6.1 | | 3(x-6)=117*13 | | -2-(-85)= | | 2x^2+7x-18=0 | | -10=(n+1)2 | | 2(n+9)=6 | | (4+3)2+(4+32)= | | 1.5f(x)=3f(.5x) | | 3.7x-3.15-1.9x=13.5 | | (x^2+y^2+1)dx+x(x-2y)dy=0 | | 1/3-5/6 | | -1/3(x-9)=-15 | | 8=sqrt(5x-1) | | 2(n-13)=6 | | sin(-x)=-cosx | | 2x+x-23=76+8x | | 6(45-u)=7 |